CONTEMPORARY PATHOGENETIC APPROACHES TO DIAGNOSIS AND TREATMENT FOR SARCOMAS OF VULVA - Ye. V. Korzhevskaya; V. V. Kuznetsov (ABV-press, 2014)
Etiology, clinical and morphologic particularities of various types of sarcomas of vulva is reviewed, their clinical classification and histopathologic grading are discussed and up-to-date pathogenetic approaches to diagnosis and treatment for sarcomas of vulva are described.